Pengaruh Kompetensi Profesional Guru PAK terhadap Hasil Belajar Siswa Kelas VIII SMP N 1 STTU Julu Tahun Pembelajaran 2023/2024 - Sabda Lestari Berutu; Rida Gultom; Franskoy Rio Naibaho (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study aims to determine the effect of PAK teacher's professional competence on the learning outcomes of VIII grade students of SMP N 1 STTU Julu in the 2023/2024 Learning Year. The research hypothesis is that there is an influence of PAK teacher's professional competence on the learning outcomes of VIII grade students of SMP N 1 STTU Julu in the 2023/2024 Learning Year. The study population was all VIII grade students of SMP N 1 STTU Julu as many as 44 people, because the subjects in this study were less than 100 so this study was a population study. Data were collected with a closed questionnaire of 20 items prepared by the author based on variable indicators according to expert theory. The questionnaire test was conducted on 32 class VIII students at Pakpak Kirana GKPPD Foundation SMPTK using 20 questionnaire items and after being tested the results of the validity of the questionnaire test were known to the value of rcount> table = 0.395-0.715> 0.349 there are 20 questionnaire items that can be used as research instruments. And the reliability of the questionnaire test which is at a value of 0.877. has been tested for validity and reliability. The results of data analysis show that there is a positive and significant influence between the influence of the professional competence of PAK teachers on the learning outcomes of students in class VIII of SMP N 1 STTU Julu Learning Year 2023/2024. With the relationship test obtained rcount> rtable, namely 0.329>0.297, with a significant relationship test tcount> ttable, namely 2.391>2.021 the coefficient of determination is 10.82%. This means that H0 is rejected and Ha is accepted. This study suggests that teachers should always improve their professional competence as a PAK Teacher, so that the learning outcomes of Class VIII students of SMP N 1 STTU Julu Learning Year 2023/2024 will be better.